When it rains, it pours: Peripartum cardiomyopathy with features of left‐ventricular noncompaction in a hemodialysis patient. Issue 4 (5th May 2016) - Antlanger, Marlies; Kammerlander, Andreas A.; Ullrich, Robert; Haidinger, Michael; Bonderman, Diana; Mascherbauer, Julia; Säemann, Marcus D.
Abstract: Pregnancy and associated pre‐eclampsia carry a high maternal risk in hemodialysis patients, yet no guidelines on how to monitor these patients' cardiovascular function exist. A 34‐year‐old hemodialysis patient presented with peripartum cardiomyopathy after a late second trimester miscarriage. On cardiac magnetic resonance imaging, diagnostic features of left ventricular noncompaction were apparent. Yet, histological and gene panel analyses remained negative. Upon stringent dry weight control and pharmacological heart failure therapy, the pathological changes showed complete regression. As pregnant hemodialysis patients have an excessively increased risk for pre‐eclampsia‐related cardiac disease, thorough screening appears valuable in these patients.